2021
DOI: 10.1016/j.eclinm.2021.100969
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of Cytosponge®-trefoil factor 3 for Barrett esophagus: A cost-utility analysis of randomised controlled trial data

Abstract: Background Esophageal adenocarcinoma has a very poor prognosis unless detected early. The Cytosponge-trefoil factor 3 (TFF3) is a non-endoscopic test for Barrett esophagus, a precursor of esophageal adenocarcinoma. Randomised controlled trial data from the BEST3 trial has shown that an offer of Cytosponge-TFF3 in the primary care setting in England to individuals on medication for acid reflux increases detection of Barrett esophagus 10-fold over a year compared with standard care. This is an econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In addition, it was shown that the interpretation of TFF3 positivity could be performed in an automated manner, thereby significantly reducing pathologist workload [39]. Further, modelling studies suggest Cytosponge TFF3-based screening to be cost-effective when used on a hypothetical population of white individuals aged ≥ 50 years with acid reflux symptoms [40,41].…”
Section: Nonendoscopic Technologiesmentioning
confidence: 99%
“…In addition, it was shown that the interpretation of TFF3 positivity could be performed in an automated manner, thereby significantly reducing pathologist workload [39]. Further, modelling studies suggest Cytosponge TFF3-based screening to be cost-effective when used on a hypothetical population of white individuals aged ≥ 50 years with acid reflux symptoms [40,41].…”
Section: Nonendoscopic Technologiesmentioning
confidence: 99%
“…In another study, the cytosponge segment size of 2 cm had a sensitivity of 90% with a specificity of 93.5% [16]. This includes the factor that there is no repetition of diagnostic procedures in examinations [14].…”
Section: Resultsmentioning
confidence: 93%
“…In another research showed gastric pain 11%, nausea or vomiting 6%, voice disturbance 3%, diarrhea or upset stomach 4%, and 1% serious adverse events such as unconsciousness and detachment of the sponge on day of the procedure. The failure to make the patient swallow CaSPER again was 19%, this was because there were no distal esophageal cells when removed [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low socio-economic status has been highlighted as a potential barrier to uptake of these new screening technologies due to lower levels of health literacy [19] . However, none of the current trials have included a detailed, individualised evaluation of multiple deprivation scores and the subsequent impact [20,21] A lack of association between cancer and deprivation in this study may be influenced by the overall low incidence of cancer detection in this unselected cohort of patients.…”
Section: Accepted Manuscriptmentioning
confidence: 99%